Enhanced Performance in Fluorene‐Free Organometal Halide Perovskite Light‐Emitting Diodes using Tunable, Low Electron Affinity Oxide Electron Injectors. (9th January 2015) - Hoye, Robert L. Z.; Chua, Matthew R.; Musselman, Kevin P.; Li, Guangru; Lai, May‐Ling; Tan, Zhi‐Kuang; Greenham, Neil C.; MacManus‐Driscoll, Judith L.; Friend, Richard H.; Credgington, Dan
<x xml:space="preserve">Abstract</x> Fluorene‐free perovskite light‐emitting diodes (LEDs) with low turn‐on voltages, higher luminance and sharp, color‐pure electroluminescence are obtained by replacing the F8 electron injector with ZnO, which is directly deposited onto the CH3NH3PbBr3 perovskite using spatial atmospheric atomic layer deposition. The electron injection barrier can also be reduced by decreasing the ZnO electron affinity through Mg incorporation, leading to lower turn‐on voltages. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>